2010
DOI: 10.1093/toxsci/kfq026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HepG2 and HepaRG by Whole-Genome Gene Expression Analysis for the Purpose of Chemical Hazard Identification

Abstract: Direct comparison of the hepatoma cell lines HepG2 and HepaRG has previously been performed by only evaluating a limited set of genes or proteins. In this study, we examined the whole-genome gene expression of both cell lines before and after exposure to the genotoxic (GTX) carcinogens aflatoxin B1 and benzo[a]pyrene and the nongenotoxic (NGTX) carcinogens cyclosporin A, 17beta-estradiol, and 2,3,7,8-tetrachlorodibenzo-para-dioxin for 12 and 48 h. Before exposure, this analysis revealed an extensive network of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
148
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 41 publications
11
148
0
1
Order By: Relevance
“…In particular, they are able to express numerous P450 cytochromes, allowing the performance of many normal metabolic liver functions such as the production of phase I and II enzymes and transmembrane transport proteins, unlike other hepatocyte cell lines such as HepG2 (Guillouzo et al 2007;Kanebratt and Andersson 2008;Turpeinen et al 2009;Jennen et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, they are able to express numerous P450 cytochromes, allowing the performance of many normal metabolic liver functions such as the production of phase I and II enzymes and transmembrane transport proteins, unlike other hepatocyte cell lines such as HepG2 (Guillouzo et al 2007;Kanebratt and Andersson 2008;Turpeinen et al 2009;Jennen et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AFB 1 alters cell cycle and apoptosis-signalling pathways in liver cell models (Ellinger-Ziegelbauer et al 2004;Li et al 2004;Tilton et al 2005;Josse et al 2012). In particular, the p53-related genes are upregulated, leading to the induction of target genes involved in cell-cycle arrest, apoptosis and stimulation of DNA repair activity (Jennen et al 2010;Josse et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The hepatotoxic properties of chemicals and drugs are usually analyzed in in vivo repeated-dose toxicity tests, which involve a high number of laboratory animals. To reduce the amount of laboratory animals, alternative in vitro models are currently developed and their screening properties evaluated [1][2][3]. Ideally these in vitro models reflect the in vivo toxicological response.…”
Section: Introductionmentioning
confidence: 99%